2012
DOI: 10.1128/jcm.05092-11
|View full text |Cite
|
Sign up to set email alerts
|

The Beginning of therpoBGene in Addition to the Rifampin Resistance Determination Region Might Be Needed for Identifying Rifampin/Rifabutin Cross-Resistance in Multidrug-Resistant Mycobacterium tuberculosis Isolates from Southern China

Abstract: We aimed to study the distribution and contribution of mutations in the rpoB whole gene in rifampin-resistant/rifabutinresistant (RIF r /Rfb r ) (or RIF/Rfb cross-resistant) clinical Mycobacterium tuberculosis isolates. One standard M. tuberculosis strain (H37Rv) and 392 other clinical M. tuberculosis isolates mainly from Guangdong Province of China whose susceptibilities to rifampin (RIF), rifabutin (Rfb), streptomycin (SM), ethambutol (EMB), and isoniazid (INH) were previously determined were subjected to DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
2
31
2
Order By: Relevance
“…This was similar to other reports (23-25) and similar to the "all pncA mutations" collected and analyzed in the TB Drug Resistance Database (http://www .tbdreamdb.com/PZA_Rv2043c_AllMutations.html), in which mutations were randomly distributed from nt 1 to nt 554. Only 13 of 44 (29.5%) mutants in this study located in the clustering of mutations of G132-T142 and P69-L85 found by previous investigators (25), which showed that the location of mutations in the pncA gene was more variable than expected before (25) and that the mutations were not clustered as in other genes associated with drug resistance, such as the rpoB gene (12). None of the isolates with identical pncA mutations were epidemiologically linked, so the PZA-resistant strains might not have been obtained from transmission.…”
mentioning
confidence: 48%
“…This was similar to other reports (23-25) and similar to the "all pncA mutations" collected and analyzed in the TB Drug Resistance Database (http://www .tbdreamdb.com/PZA_Rv2043c_AllMutations.html), in which mutations were randomly distributed from nt 1 to nt 554. Only 13 of 44 (29.5%) mutants in this study located in the clustering of mutations of G132-T142 and P69-L85 found by previous investigators (25), which showed that the location of mutations in the pncA gene was more variable than expected before (25) and that the mutations were not clustered as in other genes associated with drug resistance, such as the rpoB gene (12). None of the isolates with identical pncA mutations were epidemiologically linked, so the PZA-resistant strains might not have been obtained from transmission.…”
mentioning
confidence: 48%
“…Using LPA, these 6 strains were determined to be resistant, since both mutant and wild-type bands were absent ( Table 2). The D516G mutation occurs less frequently than D516V, is not clustered or epidemiologically significant, and has been reported to occur in isolates characterized from China, Africa, and North America (7,12,23). Similarly, an uncommon amino acid substitution was identified at position 526 in the rpoB gene product.…”
Section: Discussionmentioning
confidence: 90%
“…The three-point T m code produced by our assay either specifically identified RRDR mutations or grouped them into easily identifiable mutation clusters. This ability to subtype different RRDR mutations may prove useful in epidemiological investigations or where different rifamycins confer different levels of resistance (20,28,30,35). The assay did not depend on high-resolution T m capabilities.…”
Section: Discussionmentioning
confidence: 99%